Odpowiedzi

2010-02-16T16:11:01+01:00
A) [(3x²-xy)*-2y]*3x= (-6x²y+2xy²)*3x= -18x³y+6x²y²
b)(3x²-xy)*(-2y*3x)=(3x²-xy)* -6xy= -18x³y+6x²y²
c)[(3x²-xy)-2y] *3x= (3x²-xy-2y)*3x= 9x³-3x²y-6xy
d)(3x²-xy)*3x -2y*3x= 9x³-3x²y - 6xy
4 2 4
2010-02-16T16:14:59+01:00
A: 3x² -xy
B: -2y
C: 3x

a) (A*B)*C
b) A*(B*C)
c) (A+B)*C
d) A*C+B*C

a) ((3x² -xy) *(-2y))* 3x=(-6x²y+2xy²)*3x=-18x³y+6x²y²
b) (3x² -xy)*(-2y*3x)=(3x² -xy)*(-6xy)=-18x³y+6x²y²
c) (3x² -xy +(-2y))*3x= (3x² -xy -2y)*3x= 9x³-3x²y-6xy
d) (3x² -xy)*3x+(-2y)*3x=(3x² -xy)*3x-2y*3x=9x³-3x²y-6xy
3 2 3